2021
DOI: 10.33258/birci.v4i1.1691
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Motivation, Compensation, and Work Environment on the Performance of Local Public Officer

Abstract: The aim of this research was to find out and analyze the effects of motivation, compensation, and work environment on the performance of local public officers in the Yapen Islands Regency government environment. This research used a quantitative method and an instrument in the form of a questionnaire. Using the purposive sampling technique, 143 respondents were selected from four local government agencies in the Yapen Islands Regency. The SPSS statistical program was used to analyze data. The analysis methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 19 publications
(20 reference statements)
0
3
1
Order By: Relevance
“…Furthermore, research conducted by Widodo [7]; Munparidi [13]; Potu [1]; Raziq and Maulabakhsh [19]; Nazwirman [18] and Bashir et al [20] found that the work environment variable had a significant effect on employee performance. However, in contrast to research conducted by Arianto [21]; Sidanti [16] and Sukriyani [22] the work environment variable has no critical impact on worker performance.…”
Section: Introductioncontrasting
confidence: 66%
“…Furthermore, research conducted by Widodo [7]; Munparidi [13]; Potu [1]; Raziq and Maulabakhsh [19]; Nazwirman [18] and Bashir et al [20] found that the work environment variable had a significant effect on employee performance. However, in contrast to research conducted by Arianto [21]; Sidanti [16] and Sukriyani [22] the work environment variable has no critical impact on worker performance.…”
Section: Introductioncontrasting
confidence: 66%
“…Menurut Victuria & Hidayat (2022), generasi milenial lebih memikirkan diri mereka sendiri dan menginginkan umpan balik, pengakuan, dan pujian dari atasan mereka. Sukriyani (2021), menyimpulkan, bahwa jika seorang karyawan dibayar cukup berdasarkan pekerjaan yang karyawan lakukan untuk perusahaan karyawan akan berusaha untuk mempertahankan atau bahkan meningkatkan kinerjanya di perusahaan. Menurut Kristiani et al, (2022), dengan diberikan reward yang cukup dan adil, mereka akan puas untuk lebih meningkatkan kinerjanya guna memenuhi tujuan organisasi.…”
Section: Pendahuluanunclassified
“…Lack of knowledge, work skills and attitudes is one of the problems faced by the company, from the latest educational data it states that many employees at KSOP Class II Cirebon have a high school education background, from the results of research at TU there are employees who lack employee competence in using bisection technology. Incoming and outgoing mail input systems often experience input errors and piles of letters because these employees have low competence and skills in using computers (Sukriyani, 2021). Andthere are also employees who work beyond the predetermined job desk, employees who work not according to their fields or exceed their competency standards.…”
Section: Introduction *mentioning
confidence: 99%